OPTIMALISASI PENGELOLAAN KEUANGAN MELALUI PELATIHAN PENCATATAN DAN MANAJEMEN KEUANGAN DI RUMAH YATIM DAN DHUAFA AL-AMIEN CIATER - Rachmawaty, Rachmawaty; Novita, Dina; Lisdawati, Lisdawati (Yayasan Education and Social Center, 2024)
This article discusses a community service program aimed at enhancing the financial management capacity of the managers of Rumah Yatim dan Dhuafa Al-Amien Ciater. The problems faced by the institution, such as limited understanding of standardized financial recording systems, lack of systematic transaction documentation, and suboptimal utilization of technology in financial management, form the background for this program. The implementation methods include the preparation stage, training implementation, monitoring and evaluation, and reporting. The training is provided in 4 sessions: basics of financial management, recording financial transactions, financial reporting, and budget management. The learning methods used are interactive lectures, group discussions, case studies, hands-on practice, and financial recording simulations. The results of the activities show an increase in the participants' understanding of financial management from 45% to 85%, the implementation of a standardized financial recording system, improved efficiency in financial management, and the strengthening of the internal control system. This program is expected to have a positive impact in supporting the development and sustainability of the institution's programs in serving orphans and the poor.